Fitting In and standing out: identity and transnationalism among second-generation African immigrants in the United States. Issue 2 (4th May 2019) - Chacko, Elizabeth
ABSTRACT: This paper analyzes the ethno-national and racial identities adopted by and assigned to 1.5 and 2nd generation African immigrants and the transnational connections of this group using a focus group discussion and 30 semi-structured interviews with full-time undergraduates enrolled at universities in the Washington Metropolitan Area. Belonging was critical in framing identity for this group over the life course. An early emphasis on ethno-national African identity gave way over time to identities that more closely aligned with the realities of the second generation. During college this group sought out African-based traditions and cultures, fusing these with American sensibilities to reflect their complex and hybrid identities. Transnational connections with Africa were expressed through Afrocentric music, fashion, art and dance rather than physical movements to the continent. S⁠tudents considered themselves powerful future change agents, who through transnational activities could improve the image of Africa and help in the development of their ancestral homelands.